2009
DOI: 10.1016/j.tibs.2009.07.002
|View full text |Cite
|
Sign up to set email alerts
|

CRL4s: the CUL4-RING E3 ubiquitin ligases

Abstract: The evolutionarily conserved cullin family proteins can assemble as many as 400 distinct E3 ubiquitin ligase complexes that regulate diverse cellular pathways. CUL4, one of three founding cullins conserved from yeast to humans, uses a large β-propeller protein, DDB1, as a linker to interact with a subset of WD40 proteins that serve as substrate receptors, forming as many as 90 E3 complexes in mammals. Many CRL4 complexes are involved in chromatin regulation and are frequently hijacked by different viruses. Cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
373
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 356 publications
(379 citation statements)
references
References 100 publications
5
373
0
1
Order By: Relevance
“…More recently, Skp2 has been shown to exhibit homeostatic regulation of tumor suppressor DAB2IP and suppression of JARID1B demethylase activity in prostate carcimona. 33,34 Likewise cullin1 based E3 ubiquitin ligases, cullin4-based E3 ubiquitin ligases also play an important role in cell proliferation, DNA damage repair 7 and ubiquitylation of histone 10 via different DCAFs like Cul4-DDB1-Det1-Cop1 regulate intracellular c-jun level. 35 The present study showed that TRUSS expression peaked during the G1 phase of cell cycle and as the cells progress from G1 to S phase TRUSS level gets down-regulated coinciding with Skp2 expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Skp2 has been shown to exhibit homeostatic regulation of tumor suppressor DAB2IP and suppression of JARID1B demethylase activity in prostate carcimona. 33,34 Likewise cullin1 based E3 ubiquitin ligases, cullin4-based E3 ubiquitin ligases also play an important role in cell proliferation, DNA damage repair 7 and ubiquitylation of histone 10 via different DCAFs like Cul4-DDB1-Det1-Cop1 regulate intracellular c-jun level. 35 The present study showed that TRUSS expression peaked during the G1 phase of cell cycle and as the cells progress from G1 to S phase TRUSS level gets down-regulated coinciding with Skp2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…7 Viruses not only regulate the host-encoded E3 ligases but also encode their own Ub ligases in order to exploit the cellular homeostasis. [36][37][38][39][40] The viral HBx oncoprotein which is implicated in hepatocellular carcinoma (HCC), 41 is also known to regulate the proteasomal functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CUL4 is a member of the cullin-RING ubiquitin ligase family, the largest E3 ligase family, which appears to account for ~20% of total protein degradation by the ubiquitin-proteasome system [1][2][3]. CUL4 is conserved during evolution from yeast to human.…”
mentioning
confidence: 99%
“…In yeast, CUL4 encodes a single gene, but mammalian cells express two closely related paralogs, CUL4A and CUL4B with about 82% sequence identity. CUL4A and CUL4B assemble structurally similar E3 complexes through binding to an adaptor protein (DDB1) and a substrate receptor protein (DCAF) at the N-terminus, and a RING protein RBX1 at the C-terminus (Figure 1), and share functional redundancy in targeting substrates such as p21 and Cdt1 for ubiquitination and degradation [1,2]. The Cul4a-null mice are viable and display no abnormal development and growth phenotypes, likely due to functional compensation from Cul4b [4,5].…”
mentioning
confidence: 99%